Implementasi Sistem Deteksi Slot Parkir Mobil Menggunakan Metode Morfologi dan Background Subtraction - Rizqy Maulana; Hurriyatul Fitriyah; Esa Prakasa (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Frequently as a car driver we find it difficult to find a vacant parking slot in public places like shopping center, business, as well as institute due to the lack of information related to the availability of the parking slots in a parking lot. This can cause problems due to the driver can spend so much time just for searching the parking slot that vacant. In this research, an embedded system is proposed that can detect the availability of the parking lot that consists camera module V2 Raspberry Pi and Raspberry Pi 3. In this system also applied the morphological and background subtraction method so it can detect the total number of the parking slot and the availability of each parking slot based on the real event so the driver don't need to spend so much time just to look around for the parking slot. Based on the test on two parking lot with different parking line (straight and oblique), the system can detect the total amount of the existing parking slot based on the real condition with total accuracy rate of 100%. The system can also detect the availability of each parking slot based on the real condition with total accuracy rate of 100%.